A cross-sectional assessment of knowledge, attitude, and practice of dentists regarding acute herpetic gingivostomatitis in children (Acta Scientiarum. Health Sciences, 2025)
Acute herpetic gingivostomatitis (AHGS) is the oral manifestation of HVS-1 primary infection. Despite being a self-limiting infection, AHGS can progress to severe complications. Dentists should be prepared to correctly diagnose and treat the disease. Therefore, the purpose of this study is to assess knowledge, attitude, and practice (KAP) of dentists regarding acute herpetic gingivostomatitis (AHGS) among children. A cross-sectional and descriptive study was carried out through a KAP Survey of 416 Brazilian dentists. Descriptive analyzes with absolute and relative frequencies were performed and possible associations between socio-demographic variables with the KAP questions were investigated using Chi-square and Fisher's exact tests (significance level 5%). Results revealed high knowledge scores among 68% of the dentists. The worst knowledge scores were found for AHGS complications. High scores were only associated with degree of education (p